A KB (Royal Decree) can be withdrawn (Bulletin KNOB, 2006)
Until recently, by Royal Decree (KB) of 7 July 1903, work still proceeded on the ‘Geïllustreerde Beschrijving van de Nederlandse Monumenten van Geschiedenis en Kunst’. Thus the governmental committee defined the instruction to draw up and publish an inventory and a description of Dutch monuments and historic buildings; teams of public servants only sparsely carried out this instruction.This earliest descriptive task was aimed at distinguishing values that were of such general interest that they deserved the protection of the national government. At the time the struggle for the survival of monuments and  historic buildings primarily depended on spreading knowledge about them.Although through the years the preservation of monuments and  historic buildings continued to exist for the purpose of material continuity, the core of it shifted because of the search for cultural arguments. An important and more recent factor is the spatial context. Not only the historic building as such but also the organisation around it changed.Since 1 November 2006 there is a new organisation, the ‘Rijksdienst voor Archeologie, Cultuurlandschap en Monumenten’ (RACM), through which a domain-oriented connection has been made between archaeology, cultural landscape and historic buildings. In this same year the description of the Dutch monuments and historic buildings was completed thanks to a wider, concise inventory per province in the series ‘Monumenten in Nederland’, written by external specialists under the authority of the (former) ‘Rijksdienst voor de Monumentenzorg’ (RDMZ). The publication of the volume on the youngest province Flevoland forms the final piece and at the same time marks the turning-point in the changes in the existing order.